Duration of Static and Dynamic Periods of the Upper Arm During Daily Life of Manual Wheelchair Users and Matched Able-Bodied Participants: A Preliminary Report - Goodwin, Brianna M.; Jahanian, Omid; Cain, Stephen M.; Van Straaten, Meegan G.; Fortune, Emma; Morrow, Melissa M. (Frontiers in Sports and Active Living, 2021)
Background: Manual wheelchair (MWC) users with spinal cord injuries (SCI) are at a significantly higher risk of experiencing rotator cuff pathology than able-bodied individuals. A deeper understanding of where the arm is used dynamically within the humeral workspace during daily life may help explain why MWC users have higher shoulder pathology rates than able-bodied individuals. The purpose of this study was to report the daily percentage and consecutive durations MWC users and matched able-bodied individuals (controls) spent static and dynamic across the humeral elevation workspace. Methods: MWC users with SCI and controls wore three inertial measurement units on their bilateral arms and torso for 1 or 2 days. The percentages of time and average consecutive duration individuals were static or dynamic while in five humeral elevation ranges (0–30°, 30–60°, 60–90°, 90–120°, and >120°) were calculated and compared between cohorts. Results: Forty-four MWC users (10 females, age: 42.8 ± 12.0, time since injury: 12.3 ± 11.5) and 44 age- and sex-matched controls were enrolled. The MWC cohort spent significantly more time dynamic in 60–90° (p = 0.039) and 90–120° (p = 0.029) and had longer consecutive dynamic periods in 30–60° (p = 0.001), 60–90° (p = 0.027), and 90–120° (p = 0.043) on the dominant arm. The controls spent significantly more time dynamic in 0–30° of humeral elevation (p < 0.001) on both arms. Although the average consecutive static durations were comparable between cohorts across all humeral elevation ranges, the MWC cohort spent a significantly higher percentage of their day static in 30–60° of humeral elevation than controls (dominant: p = 0.001, non-dominant: p = 0.01). The MWC cohort had a moderate association of increased age with decreased time dynamic in 30–60° for both arms. Discussion: Remote data capture of arm use during daily life can aid in understanding how arm function relates to shoulder pathology that follows SCI and subsequent MWC use. MWC users spent more time dynamic in higher elevations than controls, and with age, dynamic arm use decreased in the 30–60° humeral elevation range. These results may exemplify effects of performing activities from a seated position and of age on mobility.